Evaluation of fourteen promising tomato lines (Solanum lycopersicum L.) as hybrids parent candidates - Rudi Hari Murti; Febiola Nindya; Enik Nurlaili Afifah; Agus Budi Setiawan (Jurnal Ilmu Pertanian, 2022)
The demand for tomato fruit has increased along with the human population. The increasing income of peoples also affect the demand orientation for high nutrition content and the shortage of resources is the obstacle for future tomato farming. Breeding tomato has been intended to create a new cultivar with high yield and quality. Previously, there were fourteen selected promising lines with high fruit firmness and yield components resulting from plant breeding program. Therefore, further steps need to be evaluated regarding yield potential and the plant quality. This study aimed to identify fourteen promising lines of high yield and high quality and compared to commercial varieties. Fourteen tomato accessions were evaluated by three control varieties. The accessions and controls varieties were assigned in a randomized completely block design (RCBD) with three replications. Data collections were analyzed using Analysis of variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT) analysis with α = 5%. Path analysis showed that the selection criteria for selecting high yield of tomato lines were fruit length, pulp thickness, fruit weight /plant, and flowers number per bunch. There were five lines of fourteen accessions which had high yield potential and four tomato lines which had worth considering fruit size and fruit firmness. These lines contained high potential characters to be used as breeding materials for improvement of hybrid.